DISHARMONI KEBIJAKAN IMPOR BERAS THAILAND KE INDONESIA TAHUN 2014-2018 - Rismudarti "; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study aims to examine the Disharmonization of Thai Rice Import Policy to Indonesia 2014-2018. The research method used is qualitative research. This research is focused on discussing the Disharmonization of Thai Rice Import Policy to Indonesia in 2014-2018. Second, researchers feel the need to provide a time limit for the phenomenon or problem to be studied, namely the years 2014-2018. This research uses the theory of liberalism. This research also uses the concept of international cooperation which is an important discussion in this research. The research data is obtained from books, journals, official documents and website that support the hypothesis. The study concludes that the Indonesian Government's interest in importing rice is driven by several policies. That is. Rice imports were carried out because rice price continued to rise, the increase in medium rice prices in recent times was due to the lack of stock in the market. What happens in the field today is that traders receive a lot of orders for medium rice even though the stock is almost empty. The supply of rice to the warehouse is small because the harvest season occurs during the rainy season. Previously, the Ministry of Agriculture had reminded the Ministry of Trade that rice imports were not necessary because the rice reserves in the warehouses of the Public Logistics Agency (Perum Bulog) were still large and also because the National Rice Production was Sufficient for Community Rice. The rice import policy from Thailand is considered to be disharmonized because the Government's data is not precise, making it difficult to validate calculations regarding the balance of staple goods. The import policy that has occurred repeatedly shows that there is no verification system for data from the Central Statistics Agency (BPS). When conducting this audit, the BPK found that there was no synchronization of data between the district and provincial BPS.Keywords: Government Policy, Disharmonization, Rice Imports